Marine radiocarbon reservoir effect of coastal waters off Cape Verde archipelago - Monge Soares, Antonio M. (2011)
Quantification of the marine radiocarbon reservoir effect (Delta R) is essential in order to calibrate conventional C-14 dates from marine shell samples with reliability. Delta R also provides information concerning the intensity of coastal upwelling in marine regions influenced by this phenomenon. C-14 ages of closely associated marine samples (mollusk shells) and terrestrial samples (goat bones) from Sao Vicente Island, Cape Verde Archipelago, permitted the first calculation of the marine C-14 reservoir effect in this region. A Delta R weighted mean value of 70 +/- 70 C-14 yr was obtained. This value is in accordance with the previously published oceanographic conditions of the region indicating the existence of a seasonal active upwelling regime.